Why nonprofit transitions fail - Dym, Barry, 1942- (FT Press Delivers elements., 2011)
This Element is an excerpt from Managing Leadership Transition for Nonprofits: Passing the Torch to Sustain Organizational Excellence (9780137047659) by Barry Dym, Susan Egmont and Laura Watkins. Available in print and digital formats. How to manage both the predictable and unpredictable challenges that derail so many non-profit leadership transitions. Leadership transitions are rarely smooth. Some difficulties are not so much due to faulty governance or planning but are natural to any major change effort. These can be anticipated and managed. Meanwhile, unforeseen events will inevitably influence board deliberations and progress. Whatever issues arise, a commitment to respond to concerns transparently gives the board credibility and room to operate....